641 CLINICAL SYMPTOM PATTERNS IN PATIENTS WITH REFLUX ASPIRATION. (17th September 2021) - Khoma, Oleksandr; Park, Jinsoo; Lee, Felix; Van der Wall, Hans; Falk, Gregory L
Abstract:  : Multiple papers have discussed pulmonary manifestation of gastro-oesophageal reflux disease (GORD), however little primary reported data exists on presenting symptoms of patients in whom reflux aspiration is confirmed. The aim of this study is to report symptoms and presenting patterns of a large group of patients with confirmed reflux aspiration. Methods: Data was extracted from a prospectively populated database of patients referred to a tertiary specialist centre with severe, refractory, or atypical reflux. Patients with reflux aspiration on scintigraphy were included in this study. Separate group included patients with evidence of proximal reflux to the level of pharynx when supine and/or upright. Results: Inclusion criteria were met by 243 patients (33% males; mean age 59). Most common symptoms amongst patients with aspiration were regurgitation (72%), cough (67%), heartburn (66%), throat clearing (65%), and dysphonia (53%). The most common two-symptom combinations were heartburn/regurgitation, cough/throat clearing, regurgitation/throat clearing, cough/regurgitation and dysphonia/throat clearing. The most common three-symptom combinations were cough/heartburn/regurgitation, cough/regurgitation/throat clearing and dysphonia/regurgitation/throat clearing. Clusters analysis demonstrated two main symptom clusters one suggestive of proximal large volume reflux symptoms (regurgitation, heartburn) and the other with IBS type symptoms (bloat, dysphagia, constipation). Conclusion: Combination of typical symptoms of GORD and a respiratory or upper aero-digestive complaint should prompt consideration of reflux aspiration. Cluster analysis of symptoms in this group supports previously postulated hypothesis of reflux aspiration pathogenesis by either large volume proximal reflux or by ineffective oesophageal motility.